2021
DOI: 10.1051/mmnp/2021001
|View full text |Cite
|
Sign up to set email alerts
|

New exact traveling wave solutions to the (2+1)-dimensional Chiral nonlinear Schrödinger equation

Abstract: In this research work, we successfully construct various kinds of exact traveling wave solutions such as trigonometric like, singular and periodic wave solutions as well as hyperbolic solutions to the (2+1)-dimensional Chiral nonlinear Schröginger equation (CNLSE) which is used as a governing equation to discuss the wave in the quantum field theory. The mechanisms which are used to obtain these solutions are extended rational sine- cosine/sinh-cosh and the constraint conditions for the existence of valid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Leta et al applied the bifurcation technique to the (2 + 1)-dimensional Bogoyavlenskii coupled system [12]. Rezazadeh et al applied the extended rational sin-cos method to the chiral nonlinear Schrödinger equation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Leta et al applied the bifurcation technique to the (2 + 1)-dimensional Bogoyavlenskii coupled system [12]. Rezazadeh et al applied the extended rational sin-cos method to the chiral nonlinear Schrödinger equation [13].…”
Section: Introductionmentioning
confidence: 99%
“…The search for different wave structures of the (2 + 1)-dimensional chiral Schrödinger equation [1][2][3][4][5][6][7] iu t + c 1 u xx + u yy + i c 2 (uu * x − u * u x ) + c 3 uu * y − u * u y u = 0 (1.1)…”
Section: Introductionmentioning
confidence: 99%
“…Osman et al [6] found a group of exact solutions of the 2D-CS equation using the Fan sub-equation method. Rezazadeh et al [7] employed the extended rational sine-cosine/sinh-cosh methods to obtain traveling wave solutions of the 2D-CS equation. Very recently, Sulaiman and his colleagues [10] considered the 2D-CS equation with variable coefficients and obtained its complex wave solutions through a series of test functions.…”
Section: Introductionmentioning
confidence: 99%
“…Also, very effective mathematical techniques have been developed and utilized for NLPDEs. Some of these techniques are the generalized Riccati equation mapping method [1,2] , the modified extended tanh expansion method combined with new Riccati solutions [3], the extended rational sine-cosine/sinh-cosh method [4,5],the modified extended tanh expansion method [6][7][8], the simplified bilinear method [9], the polynomial-function method [9,10], the Kudryashovexpansion method [9], the Riccati-Bernoulli sub-ODE technique [11,12], the Sardar-subequation method [13], the Jacobi elliptic function expansion method [14], the sine-Gordon expansion method [15], the sub-equation method [16,17], the q-homotopy analysis transform method [18], Hirotas bilinear structure [19], the Lie symmetry method [20], Haar wavelet method [21] and so on.…”
Section: Introductionmentioning
confidence: 99%